Indications and Recommendations for Tracheostomy in Trauma Population With COVID-19 Infection: A Review of the Literature. Issue 5 (May 2023) - Barbera-Mirza, Jacqueline; Chan, Kelvin; Newsome, Kevin; McKenny, Mark; Elkbuli, Adel
This review explores the current body of evidence pertaining to tracheostomy placement in COVID-19 seropositive patients and summarizes the research by tracheostomy indications, timing, and procedure. Literature review was performed in accordance with the 2020 PRISMA guidelines and includes 12 papers discussing protocols for adult patients seropositive for COVID-19. The studies demonstrated high mortality rates after tracheostomy, especially in geriatric patients, and suggested a multifactorial determination of whether to perform a tracheostomy. There was inconclusive data regarding wait time between testing seropositive, tracheostomy, and weaning off of ventilation. COVID-19 generally reaches highest infectivity between days 9 and 10; furthermore, high early mortality rates seen in COVID-19 may confound mortality implicated by tracheostomy placement. Due to the aerosol-generating nature of tracheostomy placement, management and maintenance, techniques, equipment, and personnel should be carefully considered and altered for COVID-19 patients. With surgical tracheostomy, literature suggested decreased usage of electrocautery; with percutaneous tracheostomy, single-use bronchoscope should be used. The nonemergent exchange of tracheostomy should be done only after the patient tested negative for COVID-19. Placement of tracheostomy should only be considered in COVID-19 patients who are no longer transmissible, with rigorous attention to safety precautions. Understanding procedures for airway maintenance in a respiratory disease like COVID-19 is imperative, especially due to current shortages in ventilators and PPE. However, because of a lack of available data and its likelihood of change as more data emerges, we lack complete guidelines for tracheostomy placement in COVID-19 seropositive patients, and those existing will likely evolve with the disease.